(untitled) (Journal of science and technology exploration, 2026)
This paper focuses on Japan’s bubble economy period from the mid-to-late 1980s to the early 1990s, aiming to delve into how macroeconomic prosperity systematically drove a technological paradigm shift in the field of popular music production and thereby gave birth to and defined the iconic music genre of City Pop. Rather than viewing music styles as mere cultural reflections, the study adopts an interdisciplinary approach from the intersection of technological sociology and industrial economics, demonstrating how economic capital, through the acquisition of cutting-edge equipment, restructuring of production processes, and shaping of consumer markets, completely revolutionized the infrastructure of music production. The core empirical section of the paper centers on the technological practices of two arrangers, Motoyoshi Funayama and Kyohei Tsutsumi, analyzing in detail how they, as "digital pioneers" and "fusion masters" respectively, applied computer music systems such as the Fairlight CMI, multi-track digital recording technology, and complex vocal arrangement concepts to their compositions, laying the precise and ornate auditory foundation for City Pop. Meanwhile, the study uses the production cases of top idols Nakajima Miyuki and Momoko Kikuchi as a lens to reveal how, under high-budget production models, resources were channeled into recording, arrangement, and performance to elevate idol products to the level of near-artistry. Ultimately, this paper posits that City Pop represents the "technological realization" of the bubble economy in the acoustic realm, with its rise and fall not only reflecting economic cycles but also leaving a lasting technological legacy and aesthetic symbols. It offers important insights for understanding the deep interplay between economic conditions and cultural and artistic production.